2021
DOI: 10.1111/cen.14463
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of acromegaly in moderate‐to‐severe obstructive sleep apnoea

Abstract: Method-specifi c serum cortisol responses to the adrenocorticotrophin test: Comparison of gas chromatography-mass spectrometry and fi ve automated immunoassays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In AM, the screening should be targeted, according to the presence of concomitant comorbidities and/or clinical features of AM. In Endocrine Society guidelines, it is suggested that IGF‐1 be measured in all patients with typical manifestations of AM 17 . Physicians caring for OSA patients should be aware of these features.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In AM, the screening should be targeted, according to the presence of concomitant comorbidities and/or clinical features of AM. In Endocrine Society guidelines, it is suggested that IGF‐1 be measured in all patients with typical manifestations of AM 17 . Physicians caring for OSA patients should be aware of these features.…”
Section: Discussionmentioning
confidence: 99%
“…In Endocrine Society guidelines, it is suggested that IGF-1 be measured in all patients with typical manifestations of AM. 17 Physicians caring for OSA patients should be aware of these features. In patients with OSA, it has been suggested that IGF-1 be measured only if other comorbidities, such as diabetes and hypertension, are present too.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several endocrine disorders are risk factors for OSA. Compared to the general population, patients with obesity, hypothyroidism, acromegaly, Cushing's syndrome, and type 1 and type 2 diabetes have an increased prevalence of OSA (Brúsik et al, 2016;Bruyneel et al, 2022). The prevalence of insulin resistance is also higher in non-diabetic patients with moderate-to-severe OSA (Michalek-Zrabkowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%